When Information Technology meets Healthcare in West Africa: A Literature Review - Marful, Welborn Amaoko; Winter, Alfred (Journal of Health Informatics in Africa, 2015)
Introduction: This paper presents the study and analysis of some articles that were selected according to their potential contributions to the introduction of information technology (IT) in the Healthcare industry in West Africa. A total of nineteen papers published in various journals were analysed after their titles and abstracts were reviewed.Objective: The aim of this paper is to find out on how the introduction of information technology can transform the healthcare delivery in West Africa. Methods: Keywords were used to select online articles that focus on the ways in which the use of information technology has improved or is yet to improve the provision of better healthcare in West Africa.Results and Conclusions: Information technology has a very bright future for healthcare managers, practitioners and the industry as a whole in West Africa when all the known challenges either politically-based or economy-based are removed.